Environmental Dynamics With Diarrhea Case on Toddlers - Erpita Yanti; Armaita Armaita; Aulia Asman; Linda Marni; Yessy Aprihatin (Science and Environmental Journal for Postgraduate, 2020)
Diarrhea is a disease that often occurs in toddlers both in the world and in Indonesia itself, WHO noted that diarrhea cases in infants in 2013 were 1.5 billion cases with a mortality rate of around 760,000 cases. Meanwhile, according to data from UNICEF and WHO in the same year, the death rate due to diarrhea is around 2000 toddlers each year (Craswel, 2012). The highest increase in the level of public health can be realized through the creation of the people, nation and state of Indonesia which is characterized by its population living with behavior and in a healthy environment, having the ability to reach quality health services, fairly and equally. The purpose of this study was to determine the dynamics of the cause of diarrhea in toddlers. The risk dynamics that cause diarrhea are environmental health dynamics such as the availability of sewerage (SPAL), utilization of family latrines (JAGA), utilization of clean water facilities, exclusive breast milk (ASI), washing hands after defecation or before meals, and boiling drinking water, the availability of sewerage is proven to cause diarrhea in children under five. Sanitation education environment and education or health promotion for mothers of children under five need to be improved, so as to reduce the risk of diarrhea in toddlers